Brief Eclectic Psychotherapy for Moral Trauma (BEP-MT): treatment protocol description and a case study. Issue 1 (1st January 2021) - de la Rie, Simone M.; van Sint Fiet, Antoine; Bos, Jannetta B. A.; Mooren, Nora; Smid, Geert; Gersons, Berthold P. R.
ABSTRACT: Background : Traumatic events can be related to severe transgressions or violations of moral boundaries. Moral injury (MI) has been described as 'the lasting psychological, biological, spiritual, behavioral and social impact of perpetrating, failing to prevent, or bearing witness to acts that transgress deeply held moral beliefs and expectations.' These events can provoke emotions such as remorse, guilt and shame, and affects someone's self-image and identity. Objective : The aim of the study is to evaluate a treatment protocol that addresses the specific characteristics of moral trauma in treatment of PTSD, next to anxiety. Method : Brief Eclectic Psychotherapy for Moral Trauma (BEP-MT) is an adaptation of the evidence-based Brief Eclectic Psychotherapy for PTSD (BEPP). BEP-MT integrates components of cognitive-behavioural, psychodynamic, constructivist, and systemic psychotherapy. In the current study treatment progress of a refugee Dusan was monitored. Prior to and after treatment the Clinical-Administered PTSD Scale for DSM-5, the PTSD Checklist (PCL-5), the Brief Symptom Inventory (BSI) and the Moral Injury Appraisal Scale (MIAS) were administered. Every session moral emotions were assessed on a Likert scale. Results : Whereas PTSD complaints and strong feelings of guilt and shame were manifest prior to treatment, during BEP MT a gradual decline in the intensity of the moral emotions was found. After BEP-MT Dusan no longer met criteria for PTSD and his psychological complaints diminished. Conclusion : The case of Dusan has shown it is worthwhile to address moral trauma and BEP- MT is a promising treatment protocol for patients suffering from PTSD after moral trauma. Further research is needed to examine the effectiveness of BEP-MT. HIGHLIGHTS: BEP-MT is a promising treatment protocol that addresses moral injury, which encompasses emotions such as remorse, guilt and shame, and negative self-image, after traumatic events that include transgressions or violations of moral boundaries.